2011
DOI: 10.3399/bjgp11x572689
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for ‘frequent attenders’ with medically unexplained symptoms: a randomised controlled trial (CACTUS study)

Abstract: BackgroundMedically unexplained physical symptoms (MUPS) are common and difficult to treat. AimTo investigate the effectiveness of adding fiveelement acupuncture to usual care in 'frequent attenders' with MUPS. Design and settingRandomised controlled trial in four London general practices. MethodParticipants were 80 adults with MUPS, consulting GPs ≥8 times/year. The intervention was individualised five-element acupuncture, ≥12 sessions, immediately (acupuncture group) and after 26 weeks (control group). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…[35][36][37] Consequently, a randomised trial was carried out with a nested qualitative study to investigate the effect of adding five-element acupuncture -a type of traditional acupuncture -to usual care for people who attend frequently with MUPS. The quantitative trial findings (published in this issue of the BJGP) 38 showed that a programme of 12 acupuncture sessions was acceptable and resulted in an improvement in wellbeing and individualised or health status, but no change in generic functional health or GP consultation rates.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[35][36][37] Consequently, a randomised trial was carried out with a nested qualitative study to investigate the effect of adding five-element acupuncture -a type of traditional acupuncture -to usual care for people who attend frequently with MUPS. The quantitative trial findings (published in this issue of the BJGP) 38 showed that a programme of 12 acupuncture sessions was acceptable and resulted in an improvement in wellbeing and individualised or health status, but no change in generic functional health or GP consultation rates.…”
Section: Resultsmentioning
confidence: 98%
“…38 The trial participants were adults, who were frequent attenders (eight or more consultations a year) with MUPS; they were were informed about the trial by participating London GPs. Participants were offered up to 12 individualised sessions of five-element acupuncture over a 6-month period, which was timed to meet their personal needs.…”
Section: Methodsmentioning
confidence: 99%
“…Pragmatic trials, however, are more likely to test the complex intervention as it would normally be delivered in clinical practice (for example, Paterson et al 9 ). Blinding, or the masking of patients, practitioners, outcome assessors, and statisticians about the treatment to which an individual patient has been allocated is the traditional approach to try to prevent performance and ascertainment bias in trials.…”
Section: Methodological Issues In Pragmatic Trials Of Complex Intervementioning
confidence: 99%
“…43 44 A trial investigating the effects of five-element acupuncture on patients with mainly chronic pain and 'medically unexplained symptoms' reported improvements in subjective wellbeing and, on some occasions, lifestyle changes of participants, but no change in healthcare utilisation or quality of life measures. 45 HOLDING WORK: CO-CREATING HEALTH OR FOSTERING DEPENDENCE?…”
Section: The Challenge Of Measuring Outcomes: From Surrogates To Patimentioning
confidence: 99%